The role of methionine recycling for ethylene synthesis in Arabidopsis - Bürstenbinder, Katharina; Wirtz, Markus; Hell, Rüdiger (The plant journal, 2007)
The methionine (Met) cycle contributes to sulfur metabolism through the conversion of methylthioadenosine (MTA) to Met at the expense of ATP. MTA is released as a by-product of ethylene synthesis from S-adenosylmethionine (AdoMet). Disruption of the Met cycle in the Arabidopsis mtk mutant resulted in an imbalance of AdoMet homeostasis at sulfur-limiting conditions, irrespective of the sulfur source supplied to the plants. At a low concentration of 100 μm sulfate, the mtk mutant had reduced AdoMet levels and growth was retarded as compared with wild type. An elevated production of ethylene was measured in seedlings of the ethylene-overproducing eto3 mutant. When Met cycle knockout and ethylene overproduction were combined in the mtk/eto3 double mutant, a reduced capacity for ethylene synthesis was observed in seedlings. Even though mature eto3 plants did not produce elevated ethylene levels, and AdoMet homeostasis in eto3 plants did not differ from that in wild type, shoot growth was severely retarded. The mtk/eto3 double mutant displayed a metabolic plant phenotype that was similar to mtk with reduced AdoMet levels at sulfur-limiting conditions. We conclude from our data that the Met cycle contributes to the maintenance of AdoMet homeostasis, especially when de novo AdoMet synthesis is limited. Our data further showed that the Met cycle is required to sustain high rates of ethylene synthesis. Expression of the Met cycle genes AtMTN1, AtMTN2, AtMTK, AtARD1, AtARD2, AtARD3 and AtARD4 was not regulated by ethylene. This result is in contrast to that found in rice where OsARD1 and OsMTK are induced in response to ethylene. We hypothesize that the regulation of the Met cycle by ethylene may be restricted to plants that naturally produce high quantities of ethylene for a prolonged period of time.